Mini Magazine as an Elicitor to Enhance Students’ Creativity in Writing - Yuni Astuti; Istiqomah Wulandari (Universitas Brawijaya, 2020)
Expressing ideas in the form of written expression is usually challenging for many students in ESL/EFL classes. Along with the acquisition of the second language (L2), to write in L2 students might experience some social and cognitive challenges. For instance, Students may have little confidence to write in L2 compared to that of their first language. Moreover, language proficiency in L2 adds on to the quality of good writing. Some quandaries may contribute for this situation, in writing; students may face common issues such as: grappling with grammar aspects, choosing the appropriate vocabularies, copping with punctuation and mechanics, making coherence and cohesion, and generating ideas (Al Badi, 2015; Younes & Albalawi, 2015). Thus, the researchers are going to stimulate thdents' creativity in writing via mini magazines to help students in generating their ideas and sharpen their writing skills. By assigning the students to make mini-magazines, the researchers believe that it will have a positive impact on the students' writing skills and language proficiency.